Effect of Varied Cashew Nut Ash Reinforcement in Aluminum Matrix Composite - Yallamati Abshalomu; Y. Jyothi; K. Balamurugan; Rabin Selvaraj (Advances in Materials Science and Engineering)
In the present article, cashew nut biocarbon (CTB), an agricultural waste, is used as reinforcement in Al6061 by the heating process. The primary XRD study on CTB confirms the presence of SiO2, Al2O3, iron-rich ferro-axinite, MgO, and Mn, which improve the material’s properties when used as reinforcement. SiO2 levels increase with annealing time. The extracted CTB is crushed into a ball mill for 24 hours, and the particle size is measured by SEM as 70–90 nm. An experimental study was performed with a variable percent weight of CTB with an increase of 5%–20% for structural stability applications. X-ray analysis tests the composite’s elemental composition and intermetallic elements. It confirms that no such evidence exists. CTB’s density, tensile, flexural, and impact tests measure CTB’s impact. CTB has the lowest density variation and increases tensile and flexion bearing capacity by 30% and 47%, respectively. The lightweight brittle increment is impact-resistant. SEM fracture analysis shows transgranular and intergranular fractures with dimples, large craters, and peak areas.